Revising Growth Theory in the Artificial Age: Putty and Clay Labor - Puaschunder, Julia (Archives of Business Research, 2020)
The introduction of Artificial Intelligence (AI) in our contemporary society imposes historically unique challenges for humankind. The emerging autonomy of AI holds unique potentials of eternal life of robots, AI and algorithms alongside unprecedented economic superiority, data storage and computational advantages. Yet to this day, it remains unclear what impact AI taking over the workforce will have on economic growth. This paper therefore first establishes what AI is and provides a theoretical background on standard neoclassical and heterodox economics growth theories with particular attention to the Cambridge Capital Controversy’s argument to divide capital components into fluid, hence more flexible (e.g., petty cash, checking account), and more clay, hence more inflexible (e.g., factories and intransferable means of production), components. The contemporary trend of slowbalisation is described, as the slowing down of conventional globalization of goods, services and Foreign Direct Investments (FDI) flows; yet at the same time, we still see human migration and air travel as well as data transfer continuing to rise. These market trends of conventional globalization slowing and rising AI-related industries are proposed as first market disruption in the wake of the large-scale entrance of AI into our contemporary economy. Growth in the artificial age is then proposed to be measured based on two AI entrance proxies of Global Connectivity Index and The State of the Mobile Internet Connectivity 2018 Index, which is found to be highly significantly positively correlated with the total inflow of migrants and FDI inflow – serving as evidence that the still globalizing rising industries in the age of slowbalisation are connected to AI. Both indices are positively correlated with GDP output in cross-sectional studies over the world. In order to clarify if the found effect is a sign of industrialization, time series of worldwide data reveal that internet connectivity around the world is associated with lower economic growth from around 2000 on until 2017. A regression plotting Internet Connectivity and GDP per capita as independent variables to explain the dependent variable GDP growth outlines that the effect for AI is a significant determinant of negative GDP growth prospects for the years from 2000 until 2017. A panel regression plotting GDP per capita and internet connectivity from the year 2000 to explain economic growth consolidates the finding that AI-internet connectivity is a significant determinant of negative growth over time for 161 countries of the world. Internet connectivity is associated with economic growth decline whereas GDP per capita has no significant relation with GDP growth. To cross-validate both findings hold for two different global connectivity measurements. The paper then discusses a theoretical argument of dividing labor components into fluid, hence more flexible (e.g., AI), and more clay, hence more inflexible (e.g., human labor), components. The paper ends on a call for revising growth theories and integrating AI components into growth theory. AI entrance into economic markets is modeled into the standard neoclassical growth theory by creating a novel index for representing growth in the artificial age comprised of GDP per capita and AI entrance measured by the proxy of Internet Access percent per country. Maps reveal the parts of the world that feature high GDP per capita and AI-connectivity. The discussion closes with a future outlook on the law and economics of AI entrance into our contemporary economies and society in order to aid a successful and humane introduction of AI into our world.